PEMBIAYAAN BAGI HASIL DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Yana Fajriah; Edy Jumady (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
This study aims to determine whether production sharing financing and fianancing to deposit ratio affect profitability. Data collection used secondary data and sample in the study using purposive sampling technique. The population is all Islamic commercial banks in Indonesia, amounting to 14 Islamic commercial banks, while the sample taken is 5 Islamic commercial banks. The number of samples has been tested using the classical assumption test in the form of normality test, multicolonierity test, heteroscedasticity test. The data analysis method uses multiple linear regression analysis.The results showed that the first hypothesis proposed was rejected because it showed the results of the hypothesis test of profit-sharing financing which did not have a significant effect on profitability (ROA), while the second hypothesis is rejected because the results of hypothesis testing indicate that the financing to deposit ratio has no significant effect on profitability (ROA).